2020
DOI: 10.1016/j.eucr.2019.101053
|View full text |Cite
|
Sign up to set email alerts
|

Carcino-sarcoma of the urinary bladder with cartilaginous differentiation: About a case report

Abstract: Carcinosarcoma of the bladder is a very rare and aggressive tumor with poor prognosis. We report a case of a 61 year-old-male who presented a terminal hematuria. Ultrasounds revealed a mass at the dome and the right of urinary bladder. A transurethral resection of the bladder tumor was performed. A pathological examination revealed a pT1 hight grade carciono-sarcoma of the urinary bladder with cartilaginous differentiation. Cystoprostatectomy with Bricker diversion and lymph node dissection were performed. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 4 publications
1
1
0
Order By: Relevance
“…Nazemi et al also evaluated the clinicopathological features of patients with BCS and found that patients tended to be older men who presented with advanced stage and higher grade 13 . These results are similar to our findings 6–9,14–19 . Further, Nazemi et al showed that most patients (95.9%) underwent cancer‐directed surgery, whereas only a small proportion of patients received radiation (16.7%) 13 .…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Nazemi et al also evaluated the clinicopathological features of patients with BCS and found that patients tended to be older men who presented with advanced stage and higher grade 13 . These results are similar to our findings 6–9,14–19 . Further, Nazemi et al showed that most patients (95.9%) underwent cancer‐directed surgery, whereas only a small proportion of patients received radiation (16.7%) 13 .…”
Section: Discussionsupporting
confidence: 88%
“…13 These results are similar to our findings. [6][7][8][9][14][15][16][17][18][19] Further, Nazemi et al showed that most patients (95.9%) underwent cancer-directed surgery, whereas only a small proportion of patients received radiation (16.7%). 13 We observed similar characteristics in our cohort.…”
Section: Subgroup Analysismentioning
confidence: 99%